2020
DOI: 10.1093/ageing/afaa007
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model for one- and three-year mortality in dementia: results from a nationwide hospital-based cohort of 50,993 patients in the Netherlands

Abstract: Objective to develop a model to predict one- and three-year mortality in patients with dementia attending a hospital, through hospital admission or day/memory clinic. Design we constructed a cohort of dementia patients through data linkage of three Dutch national registers: the hospital discharge register (HDR), the population register and the national cause of death register. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Our models had good predictive accuracy, as shown by the calibration plots, and the discriminative ability of the models appeared to be modest yet comparable to that of other clinical prediction models such as the Framingham Coronary Heart Disease Score. 31,32 The high shrinkage factors and low optimism in the bootstrapped Harrell c index also indicated that our developed models perform well in Swedish people diagnosed with dementia. We expect our findings to be fairly generalizable to people with dementia in other Western European countries, especially countries with similar population structures and health care systems.…”
Section: Discussionmentioning
confidence: 65%
“…Our models had good predictive accuracy, as shown by the calibration plots, and the discriminative ability of the models appeared to be modest yet comparable to that of other clinical prediction models such as the Framingham Coronary Heart Disease Score. 31,32 The high shrinkage factors and low optimism in the bootstrapped Harrell c index also indicated that our developed models perform well in Swedish people diagnosed with dementia. We expect our findings to be fairly generalizable to people with dementia in other Western European countries, especially countries with similar population structures and health care systems.…”
Section: Discussionmentioning
confidence: 65%
“…Study quality according to PROBAST criteria is shown in Table 2. Eight of the studies had concerns about applicability, either because they did not provide a usable probability table or provided only a simple cut-off with sensitivity and specificity (3 studies) [9][10][11], included hospitalized inpatients (2) [12,13], or used predictors that were difficult to obtain, poorly defined, subjective, or non-standardized (3) [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Common reasons included lack of information on discrimination and calibration, lack of internal validation, insufficient numbers of events, lack of accounting for missing data or using complete case analysis, and selecting final candidates based on the results of univariate p value testing (more details available in Supplementary Table 2). Of the 16 studies reporting model development, 2 had low risk of bias for ≥18 PROBAST signaling questions [17,18], 7 had low risk of bias for 15-17 signaling questions [9,10,12,[19][20][21], and 7 had low risk of bias for <15 signaling questions [11, 13-16, 22, 23]. The two highest quality studies were the Advanced Dementia Prognostic Tool (ADEPT) [17], derived to predict risk of death at 6 months among persons with advanced dementia in nursing homes, and a prognostic model for risk of death at 6 months among persons with dementia seen in outpatient primary care or dementia specialty clinics contributing data to a nationwide registry [18].…”
Section: Resultsmentioning
confidence: 99%
“…In 2,624 elderly nursing home patients, CCI predicted 6-month mortality [147]. In 50,993 patients with dementia, the CCI predicted 1- and 3-year survival [148]. In 1,001 elderly patients dependent on home care, the CCI predicted 1-year survival [149].…”
Section: Predictive Validitymentioning
confidence: 99%